Meningkatkan Kinerja Pemasaran melalui Orientasi Pasar dan Orientasi Kewirausahaan - Rizki Aulia; Miguna Astuti; Hariyanto Ridwan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
This study analyzes the influence of market orientation and entrepreneurial orientation on performance marketing on culinary small and medium enterpreses (SMEs) in Ciganjur region, South Jakarta. The purpose of this research was carried out to: (1) determine the influence of market orientation on performance marketing; (2) determine the influence of entrepreneurial orientation effect on performance marketing. With descriptive quantitative approach, the sampling techniques used in this research is total population sampling. The primary data are obtained through questionnaires to the 44 respondents of SMEs culinary registered in Ciganjur, South Jakarta. The tool used to analyze the data in this research is Partial Least Square (PLS) 3.0. The results obtained: (1) market orientation significantly influence the SMEs culinary’s marketing performance; (2) entrepreneurial orientation does not influence the SMEs culinary’s marketing performance.